Product Commercialisation Training for Tenants Widyatama Business Incubator (WIBI) - Keni Kaniawati; Andhi Sukma; Fansuri Munawar; Aditya Yudanegara; Rini Handayani; Sri Wiludjeung (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This study examines the pivotal role of the Widyatama Business Incubator (WIBI) in supporting MSMEs and students in enhancing their businesses through essential knowledge and training programs. WIBI's Community Partnership Programme offers training in product commercialization, HR development, SNI certification, K3L compliance, and IPR management by addressing human resource management, business licensing, and technology optimization challenges. The six-month program encompasses site inspections, coordination, training, guidance, and evaluation, enabling WIBI to standardize tenant products, improve HR quality, and ensure compliance with national standards. The program's success in facilitating the growth and success of startup ventures demonstrates the significant contribution that WIBI makes to nurturing technology-based entrepreneurship and fostering innovation within the entrepreneurial ecosystem.